KIVAEMO: A Creative Social Studies Module for Emotion Management and Anti-Bullying - Wiwin Asriningrum (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2026)
Verbal bullying and social exclusion remain significant challenges in junior high schools, affecting students’ emotional well-being, social relationships, and learning engagement. Social Studies learning has substantial potential to foster empathy and positive social behavior; however, classroom practices often emphasize cognitive achievement while providing limited opportunities for social-emotional development. This study aimed to develop and evaluate the effectiveness of KIVAEMO, a creative Social Studies module integrating emotional literacy and anti-bullying education into classroom learning. The research employed a Research and Development (R&D) approach adapted from the Sukmadinata model, consisting of needs analysis, product design, module development, expert validation, revision, limited trials, and effectiveness testing. The effectiveness test used a quasi-experimental non-equivalent control group design involving 64 seventh-grade students at SMP Negeri 1 Sanggau, West Kalimantan, Indonesia. Data were collected through emotion regulation questionnaires, anti-bullying attitude scales, expert validation sheets, and classroom observation forms. The validation results indicated that the module was highly feasible in terms of content (91%), language (90%), and instructional design (88%). Statistical analysis revealed significant differences between the experimental and control groups in emotion regulation and anti-bullying attitudes (p < 0.05), with a strong effect size (d = 0.76). Classroom observations also showed increased empathy, greater participation in discussions, and reduced verbal bullying behavior. These findings demonstrate that KIVAEMO is an effective instructional innovation that promotes emotional regulation, empathy, and positive social interaction while supporting bullying prevention efforts in junior high schools. Future studies are recommended to examine its long-term impact across broader educational contexts.